Undergraduate Nursing Students' Experiences of Conducting Clinical Research Projects in Their Bachelor Theses - a Qualitative Study - Kjersti Grønning PhD, RN; Guro Karlsholm RN; Beate André PhD, RN (SAGE Publishing, 2022)
Introduction The aim of educational institutions in the field of nursing is to educate nurses with the competences to provide high-quality care to their patients, meaning that students need to learn about evidence-based practice and how to translate the knowledge, skills, competency, beliefs, attitudes, and behaviours into daily practice. The bachelor thesis is the ultimate test for undergraduate nursing students to present what they have learned. Objective The aim of this study was to explore undergraduate nursing students' experiences of conducting clinical projects in their bachelor theses. Methods We used qualitative focus-group interviews to gain a deeper understanding of the students' experiences of conducting clinical projects in their bachelor theses as an approach to learn about evidence-based practice. The analyses focused on meaning according to Brinkmann and Kvale. Results Eighteen out of 22 eligible students who had chosen to participate in ongoing clinical research projects and write an academic paper as their bachelor thesis were included in this study. The students were all females and divided into three focus groups. The clinical projects were conducted in a public hospital, a private hospital, nursing homes, or within home-care nursing. The analyses showed that conducting clinical projects in the bachelor thesis provided the students with important knowledge for providing evidence-based care and it. motivated them to want to initiate future clinical projects as nurses., They got valuable hands-on experience for how to conduct research, and made the students aware of the importance of keeping themselves updated on the latest knowledge. Conclusion Conducting clinical research projects on a bachelor level provide undergraduate nursing students with important knowledge of how to provide evidence-based nursing care to their patients. Learning how to conduct clinical research projects is also important for motivating future nurses to initiate research aiming to improve clinical nursing practice.